Um violão poético e dançante: interpretação movida por aspectos estético-culturais conectados às tradições ashiq e aksak - Filipe Almeida Malta (2021)
The thesis proposes an investigation into the insertion and translation of rhythms and genres into the guitar that are related to folk traditions in the Balkans, Asia Minor and the Caucasus – in short, it deals with aspects of the ashiq poetic-musical genre and the rhythmic-metric system aksak. Seeking to create familiarity with the practices and materials studied, in addition to gathering fundamentals on technical-expressive issues, we started with a selection of related compositions and arrangements written by 6 guitarists: Chadas Ustuntas, Miroslav Tadić, Dušan Bogdanović, Serkan Yilmaz, Atanas Ourkouzounov and Ricardo Moyano. Interpretive concepts combine information extracted from scores, documental research, sound research and practical experiments on the instrument. For greater conceptual and methodological foundations, we dialogue with studies by several authors, such as López-Cano and Opazo (2014), Said (1990), De Assis (2018), Laranjeira (2003), Hennion (2002), Foschiera and Barbeitas (2020), Çinar (2013), Köprülü (2006), Bartók (1951 and 1976), Cohen (2007) and Arom (2004). Still, as a synthesis of the artistic process, the album Assimetrias (2021) was produced containing versions of some of the pieces examined, in addition to own arrangements and compositions that mostly emerged during the investigation.